2001
DOI: 10.1089/108497801753354285
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Tumor-Infiltrating Lymphocytes Expanded in Hollow-Fiber Bioreactors for Immunotherapy of Cancer

Abstract: We attempted to grow tumor-infiltrating lymphocytes (TIL) from 34 fresh tumors of eight different histologies using flasks for the initiation phase and hollow fiber bioreactors to expand TIL to therapeutic numbers. Overall success rate was 76% (26/34) including melanoma (9/14, 64%) and renal cell carcinoma (11/11, 100%). The mean number of days required to reach successful initiation (1 x 10(9) TIL) for all tumor types was 29 +/- 16 days (mean +/- S.D.). Therapeutic doses of TIL required an average of 88 +/- 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Stirred cultures were shown to have equal or better performance compared to static flask cultures, and could be operated at higher cell densities (Collins et al, 1998b). Other bioreactor configurations employed for the cultivation of HPC include flat bed perfusion devices (Jaroscak et al, 2003;Koller et al, 1998;Palsson et al, 1993;Sandstrom et al, 1996Sandstrom et al, , 1995, hollow fiber perfusion devices (de Kreuk et al, 2004;Knazek et al, 1990;Malone et al, 2001;Sardonini and Wu, 1993), rotating wall vessels (Liu et al, 2006), and airlift reactors (Sardonini and Wu, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Stirred cultures were shown to have equal or better performance compared to static flask cultures, and could be operated at higher cell densities (Collins et al, 1998b). Other bioreactor configurations employed for the cultivation of HPC include flat bed perfusion devices (Jaroscak et al, 2003;Koller et al, 1998;Palsson et al, 1993;Sandstrom et al, 1996Sandstrom et al, , 1995, hollow fiber perfusion devices (de Kreuk et al, 2004;Knazek et al, 1990;Malone et al, 2001;Sardonini and Wu, 1993), rotating wall vessels (Liu et al, 2006), and airlift reactors (Sardonini and Wu, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple immunohistochemical studies have described the relationship between immune-cell infiltration and tumour progression or prognosis in several cancers (Naito et al, 1998;Lespagnard et al, 1999;Ishigami et al, 2000a, b;Nakano et al, 2001;Schumacher et al, 2001). These studies have formed the basis for the practical application of immunotherapy (Malone et al, 2001;Valone et al, 2001;Ying et al, 2001;Barnea et al, 2002;Dhodapkar et al, 2002). The clinicopathological significance of infiltrating antitumour immune cells within gallbladder adenocarcinomas, however, has not been clarified.…”
mentioning
confidence: 99%
“…This 3D system evaluates controlling condition and adjusting experimental variables for optimalization of tumour cell cultures [11]. It has been already established that 3D culture in the HFBR simulates in vivo an environment and recapitulates particularly well the spatial organization of solid tumor [12]. It was shown that breast cancer cells cultured in two dimensional (2D) cultures do not recapitulate the differential structures observed in vivo.…”
Section: Discussionmentioning
confidence: 99%